Individual and Team Creativity, Leadership Style and Business Performance among SMEs in UAE: Proposed Framework - Duha Hashim Ali ALKHAZRAJI; Wan Fauziah bt Wan YUSOFF (Communications of International Proceedings, 2020)
The Government of UAE conducted many programs and incentives to support SMEs continuity.  However, the current outcome does not meet the desired objectives. Research findings statistics shows that Emirati citizens are less motivated to start SMEs business, and generally, there is the uncertainty of success due to a lack of innovativeness and leadership skills. Furthermore, SMEs faced lots of obstacles consisting of creativity, synergy, technique completion, creating an attractive business, leadership, culture, technique, prioritizing your employees, systems and methods, determining performance. This study is to explore the impact of individual creativity and team creativity on business performance; with consideration of the moderation effect of leadership style among SMEs in UAE. The proposed conceptual framework of this study has individual creativity and team creativity as predictors of business performance. Along with six leadership styles, which are individually examined as moderators to evaluate the leadership style that has the greatest significant change in the relations between creativity factors and business performance. It is to hope that the proposed framework can be tested to evaluate the current scenario of creativity, leadership style and performance of SMEs in UAE.
Keywords: Individual Creativity; Team Creativity; Business Performance; Leadership Styles; SMEs; UAE.